Designing a Novel Three-Degree-of-Freedom Parallel Robot Based on Workspace. (19th February 2016) - Fu, Jianxun; Gao, Feng
This paper presents a novel three-degree-of-freedom (3-DOF) parallel manipulator and introduces its mechanical structure. Analytical solutions of the forward kinematics have been worked out, and all configurations of this robot are graphically displayed. On the basis of several special positions in the kinematics, a task workspace is prescribed to find the smallest feasible dimensional parameters of the robot. An algorithm describing this method is also introduced. This method can easily find appropriate parameters that can size a robot having the smallest workspace enclosing a predefined task workspace. This improves the design efficiency and ensures that the robot has a small mechanical size possessing a large workspace volume and, in terms of dimension design, meets the lightweight-design requirements. With examples illustrating the design results, we further introduce a design stability in dextoensure that the robot remains a safe distance from the boundary of its actual workspace. One prototype of the robot has already been developed.